Functional limitations caused by simple bone cysts. (April 2021) - Behman, Amy; Feldman, Brian; Doria, Andrea; Fusco, Caroline; Wright, James
Purpose: Relatively little is known about the impact of benign bone lesions on function. The aim of this study was to create a more complete understanding of the impact of functional disability from simple bone cysts (SBCs) by combining qualitative and quantitative methods. Methods: This study followed a convergent parallel mixed methods design. The quantitative arm included 130 children with SBC and used the Activities Scale for Kids (ASK) to measure physical function. In the qualitative arm ten children and their parents participated in interviews related to activity participation and interactions with their physical and social environments. The two data sets were analyzed independently and then the results were integrated. Results: The ASK demonstrated 35% of children achieving the maximum score. In total, 65% of children responded "I had no medical needs" confirming that SBC, while being present throughout childhood, is largely perceived as not a chronic illness. Qualitatively most children reported minimal or no changes in activity participation but reported thinking about being more cautious during play, confirming that SBC affects effort not participation in play. Conclusion: The diagnosis of SBC did not have a significant impact on physical function, but did alter children's thoughts about physical activity participation. This finding suggests that physical function scores may have unappreciated ceiling effects. Outcome tools that combine both illness perceptions and physical function may help to better assess functional outcomes of SBC. Level of evidence: III